Analysis of the Implementation of Legal Compliance Principles in Securities Trading of Multinational Companies in Indonesia - Awandayuri Wenny Kurniasari; Andiani Putri Rahmawati (Fakultas Hukum Universitas Muhammadiyah Sorong, 2026)
This study aims to analyze the application of legal compliance principles in securities trading by multinational companies operating in Indonesia, as well as to identify the challenges faced in complying with domestic regulations. This study uses a normative juridical approach, focusing on a literature review and analysis of Law Number 8 of 1995 concerning Capital Markets. The novelty of this research lies in its emphasis on the intersection between international business practices and the Indonesian legal framework, particularly in highlighting the legal risks faced by multinational companies when operating in a regulatory environment that differs from that of their home countries. This study also offers a perspective based on the theory of legal legitimacy, which emphasizes the importance of procedural justice in encouraging voluntary compliance. Findings show that multinational companies often struggle to meet timely and accurate information disclosure requirements, which can lead to heavy sanctions and reputational damage. Insider trading cases involving these companies illustrate the detrimental impact of noncompliance on investor confidence and market integrity. The concludes that improving transparency, implementing secure reporting systems, and applying procedural justice are essential to creating a legal environment that supports compliance and strengthens confidence in the Indonesian capital market.